2005
DOI: 10.1111/j.1747-0765.2005.tb00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Iodine in a Forest Plot, an Upland Field, and a Paddy Field in the Upland Area of Tsukuba, Japan: Vertical Distribution of Iodine in Soil Horizons and Layers to a Depth of 50 m

Abstract: In the course of a series of studies conducted to investigate the long‐term behavior of 129I (which has a half‐life of 16 million years) in the environment, the vertical distribution of stable iodine (127I) in the soil horizons and layers to a depth of 50 m was determined in a forest plot, an upland field, and a paddy field in the upland area of Tsukuba, Japan. The iodine content was strongly controlled by the groundwater level and by the oxidation‐reduction conditions of the soil horizons/layers. In the fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…For instance, in Andosols, the dissolution ratio of iodine was the lowest, at pH 4.0-5.5, while above or below these pH values, in particular, above 6.0, the ratio increased by 1-2 orders of magnitude (Yuita et al 1991). The pH of soil at a depth of 0.2 m in the upland field was 6.7, a value higher than the 5.7 and 5.9 range recorded at 0-0.06 m and 0.2 m depths in the forest plot, respectively, and it was higher than the 6.0 and 6.1 range recorded at 0.5 and 1.0 m depths in the upland field, respectively (Yuita and Kihou 2005). On the other hand, on the average, 6.4% of the naturally occumng iodine in 23 soils in the U.K. was desorbed with a diluted (0.016 M) KH,PO, solution (Whitehead 1973).…”
Section: Iodine Concentration In Soil Water In a Forest Plot And An Ucontrasting
confidence: 55%
See 3 more Smart Citations
“…For instance, in Andosols, the dissolution ratio of iodine was the lowest, at pH 4.0-5.5, while above or below these pH values, in particular, above 6.0, the ratio increased by 1-2 orders of magnitude (Yuita et al 1991). The pH of soil at a depth of 0.2 m in the upland field was 6.7, a value higher than the 5.7 and 5.9 range recorded at 0-0.06 m and 0.2 m depths in the forest plot, respectively, and it was higher than the 6.0 and 6.1 range recorded at 0.5 and 1.0 m depths in the upland field, respectively (Yuita and Kihou 2005). On the other hand, on the average, 6.4% of the naturally occumng iodine in 23 soils in the U.K. was desorbed with a diluted (0.016 M) KH,PO, solution (Whitehead 1973).…”
Section: Iodine Concentration In Soil Water In a Forest Plot And An Ucontrasting
confidence: 55%
“…The study sites (a forest plot, an upland field and a paddy field) were located in the southern part of a diluvial upland area (river terrace) commonly referred to as the Tsukuba uplands, at the campus of the National Institute for Agro-Environmental Sciences (NIAES). The topography, land use, climate and vegetation of the study sites were previously reported (Yuita and Kihou 2005). Moreover, the soil profile, soil characteristics, geological stratigraphy and groundwater level of the study sites were also reported (Yuita and Kihou 2005).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…In one soil type, the soil solution concentration of organo-iodine increased 2.5 fold under flooded conditions. A very extensive sampling of iodine soil water from a forest, upland field, and rice paddy field in Japan revealed a strong negative relationship between soil Eh and soil water iodine concentrations (Yuita and Kihou, 2005). In particular, soil water iodine concentrations increase with decreasing Eh values below 200 mV.…”
Section: Influence Of Sediment Organic Matter On Iodine Sorptionmentioning
confidence: 99%